ANALYSIS ON ARTICLE 340 OF THE CRIMINAL CODE AND ARTICLE 388 OF THE CRIMINAL CODE IN THE JESSICA MIRNA CASE - Arifian Awang Budhiarta; Bardo Josua Schumacher Sitohang; Josephine Annabelle Djibu; Stevan Gabriel Louhenapessy (President University, 2022)
Murders in Indonesia vary widely. The definition of murder is a criminal act that results in the loss of a person's life. Currently, murders occur a lot in various regions in Indonesia. Apart from being influenced by motives, this is also a picture of the moral decline of this nation. It is so easy for someone to take another person's life, that the cause is worth investigating. The harshness of life and the fragility of religious education may also be factors in the ease with which someone can take another person's life. The crime of murder requires the role and duties of the authorities, namely the Police. Murder committed intentionally in its basic form is contained in Article 338 of the Criminal Code, the formulation of which is